The AMA handbook of business letters - Seglin, Jeffrey L., 1956- (AMACOM, 1996)
The second edition of The AMA Handbook of Business Letters is a complete, authoritative tool kit for writing effective business correspondence. It gives you succinct guidelines to grammar and style, plus hundreds of model letters to handle every situation that crops up in business today. And the model letters are not only pre-written, they're pre-typed. Just flip the attached diskette into any computer, and all the letters are at your disposal - keyed in and ready to go.